Investigating the Factors Affecting Grocery Sales in Itahari, Nepal - Rai, Arjun (Journal of Management, 2020)
This paper attempts to investigate the viability of small scaled grocery shops located in Itahari, Nepal. For this purpose, primary data have been collected from 39 different grocery stores using structured questionnaire. The collected data has been analysed by using SPSS-20. The research method includes both descriptive and inferential statistics for the analysis. The finding of the study shows that the average daily sales are significantly affected by the amount of capital in positive way. Similarly, the study revealed that the average daily sales are positively affected by the age of the shop, but in a statistically insignificant way.